2002
DOI: 10.1007/s00424-002-0841-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heat stress on neuromuscular activity during endurance exercise

Abstract: Aim: This study analysed the effect of hot (35°C) and cold (15°C) environments on EMG signal characteristics, skin and rectal temperatures and heart rate during progressive endurance exercise. Methods: Eight healthy subjects performed three successive 15 min rides at 30%, 50% and 70% of their peak sustained power output and then cycled at increasing (15 W/min) work rates to exhaustion in both 35°C and 15°C environments. Skin and rectal temperatures, heart rate and electromyographic (EMG) data were measured dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Both muscle and skin temperatures increased significantly as exercise progressed under all conditions, but these values were significantly higher in H+H than in both HYP and NOR. Heat stress was rather modest in the present study (32 • C) compared with previous studies (>35 Hunter et al, 2002;Lorenzo et al, 2010;Guy et al, 2016). However, in H+H, muscle and skin temperatures reached 38.1 ± 0.1 • C and 36.2 ± 0.2 • C, respectively, by the end of exercise.…”
Section: Discussioncontrasting
confidence: 74%
“…Both muscle and skin temperatures increased significantly as exercise progressed under all conditions, but these values were significantly higher in H+H than in both HYP and NOR. Heat stress was rather modest in the present study (32 • C) compared with previous studies (>35 Hunter et al, 2002;Lorenzo et al, 2010;Guy et al, 2016). However, in H+H, muscle and skin temperatures reached 38.1 ± 0.1 • C and 36.2 ± 0.2 • C, respectively, by the end of exercise.…”
Section: Discussioncontrasting
confidence: 74%
“…The third important Wnding was that in all conditions, HR did not change signiWcantly between the second and the last repetition, conWrming that cardiovascular drift did not occur as a result of Xuid loss and associated mechanisms to maintain cardiac output and to dissipate heat (Hunter et al 2002;Baron et al 2008). Moreover, HR and did not reach maximal values during the Wnal interval indicating that muscular parameters and not the cardiovascular response regulated the sprinting performance (Young et al 1995;Chelly and Denis 2001).…”
Section: Discussionmentioning
confidence: 88%
“…Whilst some studies have observed a decrease in electromyographic (EMG) activity while cycling in hot ambient conditions (Kay et al 2001; Tucker et al 2004; Tucker et al 2006), others have reported that EMG activity was not affected during running (Ftaiti et al 2001) and cycling (Hunter et al 2002). However, it is difficult to interpret such EMG data during whole-body dynamic exercise as modifications in EMG activity may be linked to alterations in exercise modality, pattern and intensity.…”
Section: Introductionmentioning
confidence: 99%